2012
DOI: 10.1007/s10875-012-9754-4
|View full text |Cite
|
Sign up to set email alerts
|

Human Chitotriosidase: a Sensitive Biomarker of Sarcoidosis

Abstract: Chitotriosidase proved to be a biomarker with good sensitivity and specificity that is easily detected in serum. It can be proposed in clinical practice to identify progressive patients requiring close follow-up, to detect relapses and to evaluate the effects of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
82
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 29 publications
8
82
0
1
Order By: Relevance
“…Lipid accumulation promotes gene expression in macrophages, affecting the inflammatory process that occurs in atherogenesis [33] . Higher concentrations of chitotriosidase have been reported in the serum of patients with atherosclerosis than in controls (55-fold increase) as well as in sarcoidosis patients [29][30][31][32] . Chitinase 1 plays a role as inflammatory and profibrotic molecule in both diseases, suggesting that it may be a useful disease biomarker and indicator of atherosclerotic plaque formation, as well as in pulmonary granulomatous inflammation [34][35][36] .…”
Section: Chitotriosidase In Atherosclerosis and Sarcoidosismentioning
confidence: 97%
See 1 more Smart Citation
“…Lipid accumulation promotes gene expression in macrophages, affecting the inflammatory process that occurs in atherogenesis [33] . Higher concentrations of chitotriosidase have been reported in the serum of patients with atherosclerosis than in controls (55-fold increase) as well as in sarcoidosis patients [29][30][31][32] . Chitinase 1 plays a role as inflammatory and profibrotic molecule in both diseases, suggesting that it may be a useful disease biomarker and indicator of atherosclerotic plaque formation, as well as in pulmonary granulomatous inflammation [34][35][36] .…”
Section: Chitotriosidase In Atherosclerosis and Sarcoidosismentioning
confidence: 97%
“…Atherosclerosis is associated with accumulation of lipids in artery walls after deposition of LDL cholesterol and fibrous matrix. In the early stage of this disease, monocytes differentiate into foam cells (lipidloaded macrophages generated by massive uptake of modified LDL) that take part in inflammatory responses and tissue remodeling in the arterial intima (vessel lumen narrowing and intimal thickening associated with increased risk of thrombosis) [29][30][31][32] . Lipid accumulation promotes gene expression in macrophages, affecting the inflammatory process that occurs in atherogenesis [33] .…”
Section: Chitotriosidase In Atherosclerosis and Sarcoidosismentioning
confidence: 99%
“…Consequently CHIT-1 is used as a highly specific biomarker for lysosomal storage disorder [14]. Later the levels of this enzyme were found elevated in Niemann-Pick diseases [15], but also in other pathological conditions including β-thalassaemia [16], sarcoidosis [17], multiple sclerosis [18], atherosclerosis [10] and in parasitic infections such as plasmodium falciparum malaria [19]. Interestingly, other investigations have suggested that CHIT-1 may be involved in the progression of nonalcoholic steatohepatitis [20,21] and could have a crucial role even in pathological conditions, such as coronary artery disease [22], acute ischemic stroke [23] cerebrovascular dementia (CVD) and Alzheimer's disease (AD) [24].…”
Section: Introductionmentioning
confidence: 99%
“…We did not consider persistent disabling symptoms such as fatigue, small-fibre neuropathy, cognitive dysfunction, depression and impaired quality of life, which may be at the forefront for many patients with sarcoidosis [40][41][42][43][44][45]. We did not consider new biomarkers [46] or FDG-PET, which is used only in certain circumstances [47,48]. Currently, the main uses for FDG-PET are in 1) helping find a site for biopsy in difficult cases, 2) investigation of cardiac sarcoidosis [48], 3) searching for active pulmonary lesions in advanced fibrotic pulmonary sarcoidosis, and 4) searching for metabolic activity in patients with persistent disabling symptoms and normal biomarkers, i.e.…”
Section: Discussionmentioning
confidence: 99%